Perbedaan Kadar Hemoglobin dan Lingkar Lengan Atas Ibu Hamil antara Anak Bawah Dua Tahun (BADUTA) Stunting dan Normal - Tika Noor Prastia; Rahma Listyandini (State Islamic University of Sunan Ampel, 2020)
Stunting is a chronic malnutrition that occur intergeneration. Mothers who experience with malnutrition are giving children at risk of stunting. This condition contributes to decreasing the quality of human resources and increasing morbidity and mortality. The purpose of this study was to determine differences in hemoglobin levels and upper arm circumference of pregnant women between stunted and normal in children under two years in the working area of Cibungbulang Public Health Center, Bogor Regency. The research design was descriptive analytic with cross sectional approach. The total sample of 115 respondents obtained by purposive sampling technique. The results showed that there were no differences in hemoglobin levels (p-value = 0.835) and upper arm circumference (p-value = 0.114) during pregnancy between stunting and normal children under 2 years. Stunting needs to be more focused not only on the pre-conception period but the improvement of nutrition during the first 1000 days of life because this period is a catch-up period and determines the quality of the individual in the next phase of life.